2021
DOI: 10.7717/peerj.10579
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the mating system and patterns of contemporary pollen flow in trees of the genus Anadenanthera (Fabaceae)

Abstract: Anadenanthera (Fabaceae) is endemic to the Neotropics and consists of two tree species: A. colubrina (Vell.) Brenan and A. peregrina (L.) Speg. This study examined the mating system and contemporary gene flow of A. colubrina (Acol) and A. peregrina (Aper) in a highly fragmented area of the Atlantic Forest to provide valuable information that informs conservation strategies. Reproductive adults from forest remnants [nA. colubrina = 30 (2.7 ha), nA. peregrina = 55 (4.0 ha)] and progeny-arrays (nA. colubrina = 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Specifically, seedlings with only one putative parent identified within the population were presumed to represent the distance of seed dispersal, assuming that pollen dispersal distances are more likely to come from geographically more distant reproductive trees that were not sampled ( Dow and Ashley, 1996 ). For seedlings with two putative parents identified among the reproductive trees of the study population, the one nearest to the seedling was presumed to reflect seed dispersal (i.e., the maternal parent), whereas the more distant one was presumed to reflect pollen dispersal (i.e., the paternal parent), again using the assumption that the distance traveled by pollen is likely greater than that of seeds, which has been applied in parentage analyses when the maternal parent is not distinguishable (e.g., Dow and Ashley, 1996 ; Guidugli et al, 2016 ; Feres et al, 2021 ), as is the case of the hermaphroditic tree species such as D. jueirana-facao . We also calculated seed ( m s ) and pollen ( m p ) immigration rates.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, seedlings with only one putative parent identified within the population were presumed to represent the distance of seed dispersal, assuming that pollen dispersal distances are more likely to come from geographically more distant reproductive trees that were not sampled ( Dow and Ashley, 1996 ). For seedlings with two putative parents identified among the reproductive trees of the study population, the one nearest to the seedling was presumed to reflect seed dispersal (i.e., the maternal parent), whereas the more distant one was presumed to reflect pollen dispersal (i.e., the paternal parent), again using the assumption that the distance traveled by pollen is likely greater than that of seeds, which has been applied in parentage analyses when the maternal parent is not distinguishable (e.g., Dow and Ashley, 1996 ; Guidugli et al, 2016 ; Feres et al, 2021 ), as is the case of the hermaphroditic tree species such as D. jueirana-facao . We also calculated seed ( m s ) and pollen ( m p ) immigration rates.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses revealed that A. colubrina is a mixed mating species (multilocus outcrossing rate = 0.619) while A. peregrina is a predominantly outcrossing species (multilocus outcrossing rate = 0.905). For both species, high indices of biparental inbreeding were observed (0.159 and 0.216 respectively), resulting in low effective pollination neighborhood sizes (Feres et al 2021). Sujii et al (2017) used nuclear and plastid microsatellite markers to assess genetic parameters of juvenile and adult individuals in two Centrolobium tomentosum restoration areas, one corresponding to a disturbed fragment and the other, a large and well-preserved protection area.…”
Section: Atlantic Forest Biomementioning
confidence: 99%
“…Such a wide range in outcrossing rates for mixed-mating species are common and can change over time and space due to environmental conditions and intrinsic population features, such density and demographic structure (e.g., Wright et al, 2013). As with M. catharinensis, high outcrossing rates have been reported for many Neotropical plant species (e.g., Ward et al, 2005;Feres et al, 2012Feres et al, , 2021Nazareno and Reis, 2012;Spoladore et al, 2017;Godoy et al, 2018;Montagna et al, 2018;Sujii et al, 2021), including two congener Mimosa species (Moreira et al, 2011;Arruda et al, 2020). Studies on populations of M. scabrella (Arruda et al, 2020), for instance, showed a similar reproductive pattern with high outcrossing rates (t = 0.925/0.845) and low estimates of selfing (s = 0.075/0.155).…”
Section: Inbreeding and Mating System Of Mimosa Catharinensismentioning
confidence: 99%